Dakwah Kultural Sunan Kalijaga: Tinjauan Epistemologi Bayani, Burhani, dan Irfani - Nurul Lathifah; Abdul Latif; Roshifah Jauhari; Nur Cholid (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Sunan Kalijaga played an important role in the development of Islam, especially in Java. The name Lokajaya is attached to Sunan Kalijaga when preaching choosing to use culture and art. Wayang art is one of the things used in preaching so Sunan Kalijaga is known as a puppeteer of wayang purwa. Epistemology in Islam uses empiricism and rationalism as the foundation of true epistemology, but in Islamic epistemology it also uses God's word and intuition as a source of knowledge. Oneof the Muslim thinkers Muhammad 'Abid Al-Jabiri divided thepistimology in Islam into three methods, namely the bayani, burhani, and irfani methods. This research is using research with qualitative descriptive methods, the purpose of this method is to provide a general explanation of Sunan Kalijaga's cultural da'wah. This article uses a Library Research approach or literature research which is a study that examines various reference materials and findings related to previous research and serves to build a theoretical foundation for the problem being investigated (Sarwono: 2006). Data collection techniques use documentation procedures. Data analysis is carried out by comparing different pieces of documentation literature with different data from research findings related to the topic of research publication. Keywords: Da'wah, Sunan Kalijaga, Epistimology